Structural studies of pestivirus envelope glycoproteins - Aitkenhead, H (2021)
Pestiviruses belong to the family Flaviviridae with the most well-known being Bovine Viral Diarrhoea Virus, Border Disease Virus, and Classical Swine Fever Virus affecting cows, sheep, and pigs respectively. These viruses cause a large economic impact especially in the dairy and pig industries. As a result of being enveloped viruses, to enter the cytoplasm and replicate, they must first fuse their membrane with that of the cell’s endosome, in a process which requires a fusion protein. Pestiviruses require two envelope glycoproteins for this step: E2, likely involved with receptor interaction, and E1, likely the fusion protein.